Implications of AI Based as Learning Media to Improve the Speaking Skill From Perspective Students at STIKOM Tunas Bangsa ; Trough Mobile Assisted Language Learning - Sormin, Rizky Khairunnisa; Sari, Ika Purnama; Purba, Anita; Rizki, Fitri (Journal of Educational Sciences, 2025)
This research is based on the urgency of utilizing technology in education, which has now become a necessity rather than relying on traditional methods that are still widely used in teaching information systems students. In the context of using English as a global communication tool in the digital era, conventional teaching approaches are considered less effective in keeping up with the rapid development of information. Therefore, this study explores the implication of Artificial Intelligence (AI) based learning media in improving students’ speaking skills through Mobile-Assisted Language Learning (MALL) at STIKOM Tunas Bangsa. The research employs a qualitative –descriptive method involving fourth-semester students who actively use AI-powered mobile applications, such as speech recognition and virtual conversation tools. Data were collected through interviews, questionnaires, and observations to captured students’ perspectives on the effectiveness, accessibility, and challenges of using AI in language learning. Findings reveal that most students perceive AI-based media as motivating and helpful in enhancing pronunciation, fluency and confidence. Additionally , this study provides insights into the sociolinguistic evolution of language use by examining how students interact with technological advancements and adapt to global communication demands. The results suggest that AI-integrated MALL can significantly support speaking skill development and create a more personalized, effective, and engaging learning environment.